1971
DOI: 10.1002/ar.1091700407
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial cell proliferation in the mouse vagina during the estrous cycle, pregnancy and lactation: A radioautographic study

Abstract: A radioautographic study of epithelial cell proliferation in the vaginas of mice during the estrous cycle, pregnancy, lactation, and under certain experimental conditions is reported. Data were expressed as labeled cells per 1000 basal cells counted. The proportion of labeled cells that were basal or nonbasal was determined. The highest rates of proliferation were recorded during the estrous cycle, specifically during late diestrus, proestrus and early estrus. During pregnancy the rates of proliferation increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1972
1972
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…The variation of E2 during gestation in Mongolian gerbils is similar to those in rats and mice, in which the E2 level gradually increases during early gestation, reaching a peak during embryo implantation, and then continuously increases, reaching a peak before parturition [3,15,26,32]. In the present study, the pattern of P4 levels during gestation was similar to those observed in previous works [11,12], but differed from those detected in rats and mice.…”
Section: Hormonal Variations During Gestation In Primiparous Mongoliasupporting
confidence: 88%
“…The variation of E2 during gestation in Mongolian gerbils is similar to those in rats and mice, in which the E2 level gradually increases during early gestation, reaching a peak during embryo implantation, and then continuously increases, reaching a peak before parturition [3,15,26,32]. In the present study, the pattern of P4 levels during gestation was similar to those observed in previous works [11,12], but differed from those detected in rats and mice.…”
Section: Hormonal Variations During Gestation In Primiparous Mongoliasupporting
confidence: 88%
“…The generative compartment is a homogeneous population of actively proliferating cells. The same basal cells can give rise to either a stratified squamous keratinized or a nonkeratinized epithelium [Barker and Walker, 1966;Traurig, 1971;Montes and Luque, 1988]. Keratohyalin and MCGs and the resulting barrier formation are organelles produced in the stratum spinosum and granulosum cells [Westerhof and Dingemans, 1987].…”
Section: Discussionmentioning
confidence: 99%
“…Vaginal epithelial differentiation and its hormonal regulation have been analyzed in detail by autoradiography (Galand et al, 1971;Traurig, 1971;Husbands and Walker, 1963), electron microscopy (Hayashi et al, 1988;Eddy and Walker, 1966). histochemistry (Putti and Varano, 1979;Green, 1959), and in tissue culture (Cooke et al, 1986;Iguchi et al, 1983).…”
Section: Introductionmentioning
confidence: 99%